Gingivitis: A Common Preventable Oral Health Problem (TAJ: Journal of Teachers Association, 2009)
Bangladesh is a country possessing harmful lifestyle for oral health. The country culture put the people to be exposed to harmful factors responsible for development of gingivitis. However, effective health education can bring encouraging result to aware them for healthy practice. The objective of the present study is to investigate the effect of habitual factor as well as demographic influence on gingival health status. A hospital-based cross sectional descriptive study was carried out at the Faculty of Dentistry, BSMMU, Dhaka-1000, from April-June of 2004. A total of 117 cased were interviewed and examined. Data were collected from all patients attended the dental outpatient department. All patients were interviewed (face-to-face) using a semi-structured questionnaire. Clinical examination was performed to measure the gingival health status using standard gingival index. Statistical analysis was carried out using SPSS program version 10.0. Among all participants 37.6% were female and 62.4% were male. The age range of the participants was 10-65 years. Most of the participants were student (22.2%). The study showed high rate of gingivitis (89%). The peak prevalent age group was over 40 years. The worst condition was detected among those who were both tobacco users as well as betel nut chewers (73.3%) and this is highly significant (p